2013
DOI: 10.1021/cm401709d
|View full text |Cite
|
Sign up to set email alerts
|

Organic Dots with Aggregation-Induced Emission (AIE Dots) Characteristics for Dual-Color Cell Tracing

Abstract: Modern fluorescence imaging techniques have become essential tools to provide crucial insights in understanding complicated biological processes. Because of their unique optical properties (e.g., excellent photostability, high brightness, broad absorption, and narrow emission), inorganic quantum dots (QDs) have attracted great interest in fluorescence bioimaging. However, the intrinsic toxicity resulting from their heavy-metal components as well as the low-pH-induced fluorescence-quenching phenomenon has motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 22 publications
1
86
0
Order By: Relevance
“…Using similar strategies, 30 nm NPs based on fluorogen AIE6 were also obtained. These NPs displayed a QY of 58% with an extinction coefficient ≈ 4 × 10 7 M −1 cm −1 . Although the AIE dye content inside these NPs cannot be easily estimated, it is expected that the particle core is composed of pure dye (Figure ), in contrast to conventional dyes highly diluted in the polymer matrix.…”
Section: Dye Design and Encapsulation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using similar strategies, 30 nm NPs based on fluorogen AIE6 were also obtained. These NPs displayed a QY of 58% with an extinction coefficient ≈ 4 × 10 7 M −1 cm −1 . Although the AIE dye content inside these NPs cannot be easily estimated, it is expected that the particle core is composed of pure dye (Figure ), in contrast to conventional dyes highly diluted in the polymer matrix.…”
Section: Dye Design and Encapsulation Strategiesmentioning
confidence: 99%
“…[88a] Unfortunately, the data on photostability of NPs is much less systematic and is difficult to compare, as they were performed on different setups using different illumination powers. In the case of dye AIE1, it was shown that photobleaching was observed within the time scale of 100 s with a relatively large total number of collected photons (4.4 × 10 7 ) . We also studied photostability of PDI based PLGA NPs at the single particle level.…”
Section: Control Of Np Propertiesmentioning
confidence: 99%
“…Thus, the present work shows the crucial role of counterion fluorination in achieving high fluorescence brightness and photostability, narrow-band emission, efficient energy transfer and high intracellular stability of nanomaterials for light harvesting and bioimaging applications. 10,11,[15][16][17] Conjugated polymer NPs are probably the brightest organic nanomaterials, 6, 18 19 but, they lack biodegradability, due to their polymer backbone made from carbon-carbon bonds. Dye-based NPs are of particular interest because of their very high density of fluorophores per volume compared to dyedoped (blended) systems, where the dye is diluted in a matrix.…”
mentioning
confidence: 99%
“…In fact, previous reports have shown that the aggregation degree of AIEgens will lead to an increase in THG and THG-induced fluorescence in a process known as aggregation-induced THG enhancement. 63 Future studies will be carried out to confirm if these characteristics hold true for TPE-TETRAD NPs. Furthermore, the bioimaging applications of TPE-TETRAD NPs based on 3PL and THG features will be explored in future studies.…”
Section: Resultsmentioning
confidence: 95%